Turkish Gastroenterology Association, Pancreas Study Group, Chronic Pancreatitis Committee Consensus Report - Soytürk, Müjde; Bengi, Göksel; Oğuz, Dilek; Kalkan, İsmail Hakkı and Yalnız, Mehmet and Tahtacı, Mustafa and Demir, Kadir and Kasap, Elmas and Oruç, Nevin and Ünal, Nalan Gülşen and et al. (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Soytürk M, Bengi G, Oğuz D, et al. Turkish Gastroenterology Association Pancreas Study Group Chronic Pancreatitis Committee Consensus Report. Turk J Gastroenterol 2020; 31(Suppl 1) S1-41.